The marvellous travels of Fernando Mendez Pinto across the low lands:translation, appropriation and reception - Couto, Patricia (2012)
Tese de doutoramento, Estudos de Literatura e de Cultura (Estudos Comparatistas), Universidade de Lisboa, Faculdade de Letras, 2012